Solution processing of highly conductive ruthenium and ruthenium oxide thin films from ruthenium–amine complexes1. Issue 17 (7th May 2015) - Murakami, Yoshitaka; Li, Jinwang; Hirose, Daisuke; Kohara, Shinji; Shimoda, Tatsuya
<x xml:space="preserve">Abstract</x> Designing of ruthenium–amine complexes leads to preparation of highly conductive thin films of ruthenium (20–40 nm thick) and ruthenium oxide (50–90 nm thick) by a simple solution process.